Show Me What You’ve B/Seen: A Brief History of Depiction - Beukeleers, Inez; Vermeerbergen, Myriam (Frontiers in Psychology, 2022)
Already at a relatively early stage, modern sign language linguistics focused on the representation of (actions, locations and motions of) referents 1) through the use of the body and its different articulators and 2) through the use of particular handshapes. Early terminology for 1) includes role playing, role shifting and role taking and for 2) classifier constructions/predicates and verbs of motion and location. More recently, however, new terms, including enactment and constructed action for 1, and depicting signs for 2) have been introduced. This paper investigates the various theoretical evolutions in the thinking about role shifting and classifier constructions and the concomitant terminology shifts. Subsequently, we investigate the relation between role shifting and constructed action. While doing so, we question the idea that these terms can be used interchangeably, and we rather suggest that these terms capture different, but related functions. Finally, we also investigate the method, i.e. function, of depicting. Where previous research often associates this method with the use of partly-lexical classifier constructions and bodily enactment, we argue that depicting is a semiotic diverse practice and thus suggest that signers can use different signs of different types when building a depiction. In this way, this paper does not only provide a brief overview of the history of depiction in the sign linguistic literature, but it also point towards 1) the risks that may come with the execution of terminology shifts and 2) the importance of making a clear distinction between form and function and/or caution when assuming a (too) exclusive relation between a certain function and particular forms.